Working Collaboratively in Hospice and Palliative Care - Sharing Time - McDonald, Christine (Auckland University of Technology, 2018)
Palliative care is the physical, social, emotional, and spiritual care of people with a life-limiting illness (Palliative Care Subcommittee, 2007). As a health care service, palliative care advocates for a holistic multidisciplinary approach. While service delivery is certainly multidisciplinary, whether health professionals working in New Zealand palliative care services practice collaboratively, and in what form that collaboration takes, is unknown. Collaborative practice can be difficult to achieve, as traditionally trained health professionals are more accustomed to working alongside each other, rather than together (Herbert, 2005; Herbert et al., 2007). Gaining further knowledge about what is occurring in practice is important when, driven by international workforce shortages and an increasing complexity of health care, the World Health Organisation (WHO) (WHO & Health Professions Network Nursing and Midwifery Office: Department of Human Resources for Health, 2010) has called for interprofessional education and collaborative practice across all areas of health care. Glaserian grounded theory methodology has been used to examine the area of interest which is, ‘What is the main concern of health professionals working collaboratively in palliative care (with colleagues and patients) and how do they manage that?’ A total of 25 interviews were undertaken with 23 participants, across professional disciplines, working in palliative care services within the North Island of New Zealand. Through an iterative process of constant comparative analysis and conceptualisation, using memoing, key concepts, and abstracting categories, a theory emerged. The theory of Sharing Time explained the social process of how health professionals working collaboratively in palliative care facilitated collaboration, while managing their main concern. Sharing Time is both an interactive participatory process and an outcome. The main concern of possessorship, is defined as having possession of a tangible commodity or having a need to have possession of an intangible commodity, that has the potential to impact patient care when not shared. Sharing Time occurs when health professionals purposefully make time, take time, find time, and spend time in their workday for and with each other, to share further, and facilitate collaboration. Sharing Time occurs through purposeful connecting and finding common ground. Integrated by reciprocity this theory is mutually beneficial to all involved as there is an exchange of a commodity, such as equipment or information, which improves patient care. This research also discovered that health professionals Sharing Time are facilitating collaboration by situating this strategy in a middle ground. Moving outside of this middle ground, where there is too much or too little Sharing Time, continues the main concern of possessorship rather than manages it, which adds barriers to collaboration. The theory of Sharing Time has potential value for all health professionals working in palliative care, as it facilitates collaboration and promotes further sharing. Collaboration and managing possessorship promotes a safer work environment.
Keywords: Sharing time; Possessorship; Hospice; Palliative care; Collaboration